2016
DOI: 10.1021/acs.jctc.6b00805
|View full text |Cite
|
Sign up to set email alerts
|

Multiconformation, Density Functional Theory-Based pKa Prediction in Application to Large, Flexible Organic Molecules with Diverse Functional Groups

Abstract: We consider the conformational flexibility of molecules and its implications for micro- and macro-pK. The corresponding formulas are derived and discussed against the background of a comprehensive scientific and algorithmic description of the latest version of our computer program Jaguar pK, a density functional theory-based pK predictor, which is now capable of acting on multiple conformations explicitly. Jaguar pK is essentially a complex computational workflow incorporating research and technologies from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
199
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(200 citation statements)
references
References 98 publications
1
199
0
Order By: Relevance
“…CO 2 and O 2 reduction). [45,46] A reliable ab initio method to calculate deprotonation free energies would provide an improvement upon existing computational approaches to determining pKa's and protonation states, [47][48][49] which would have significant ramifications for drug discovery, [50,51] materials science, [52][53][54] and the structural determination of biological complexes. [55,56] In the context of chemical catalysis, proton removal is known to be the rate-limiting step in many important reactions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 and O 2 reduction). [45,46] A reliable ab initio method to calculate deprotonation free energies would provide an improvement upon existing computational approaches to determining pKa's and protonation states, [47][48][49] which would have significant ramifications for drug discovery, [50,51] materials science, [52][53][54] and the structural determination of biological complexes. [55,56] In the context of chemical catalysis, proton removal is known to be the rate-limiting step in many important reactions, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A high degree of prediction accuracy in modern terms is considered to be within 1 pK a unit per prediction, with a mean absolute error (MAE) for a test set of less than 0.5 units. 35 As the Table 1 pK a values of aryl/pyridinyl guanidines and iminoimidazolidines calculated using AIBLHiCos and determined experimentally by potentiometric and spectrophotometric methods…”
Section: Validation Of the Aiblhicos Prediction Methods Applied To Arymentioning
confidence: 99%
“…This is again an approximation as previous work by Bochevarov et.al. [11] have shown that multiple low lying conformations do contribute to the deprotonation free energy. There can be a couple of different strategies to handle this phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Machine learning models for specific functional groups are trained based on these descriptors [10]. Notably, these methods ignore the three dimensional conformation of the compound explicitly [11]. Although training the models might be expensive in terms of curating experimental pKa data for generating appropriate models, subsequent pKa prediction using trained models can be very fast and inexpensive.…”
Section: Introductionmentioning
confidence: 99%